Synthesis and Characterization of TiO2 Nanoparticle as Adsorbent on The Treatment of Methylene Blue Dye Pollutant - Thahir, Ridhawati; Wahab, Abdul Wahid; Nafie, Nursiah La; Raya, Indah (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2019)
The dye of methylene blue (MB) is organics pollutant from chemical industries. The parameter of MB content are available as methylene blue active substance (MBAS) do not exceed 200 g/L. The treatment of MB dye pollutant can be done by adsorption process with TiO2 nanoparticle. This aim of this research was synthesized of TiO2 nanoparticle using PVA as surfactant and titanium tetraisoproxide (TTIP) as titanium source through sol-gel preparation to hydrothermal process at temperature 400 and 600oC. The result of XRD spectrum was shown the tetragonal crystal, the phase of anatase, and the size of particle was 1.66 to 3.15 nm. Infrared spectroscopy of Ti-O functional group was at 467 cm-1 and there were hydroxyl groups of the surface TiO2. DSC analysis was indicated the thermal stability of TiO2 at 250oC. Application of TiO2 nanoparticle as an adsorbent to photodegradation of MB with Hg lamp 150 watt during 60 minutes. The highest of adsorption capacity at the sample TiO2-600 was 217 mg/g and effectiveness adsorption was 81%. Isoterm adsorption process of MB by TiO2 nanoparticle can be obtained with Langmuir and Freundlish equation, with the determined coefficient value were close to 1. These results suggest of TiO2 nanoparticle was indicated highly potential to apply for the treatment of pollutant industries.